The Burden of a Second Mandate - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The overwhelming affirmative vote given to the 1986 Constitution in the February plebiscite may be seen as a testimony to Cory Aquino's unfading popularity. Viewed against the background of the recent military-led attempts to overthrow her government, the vote signifies an unequivocal rejection of Marcos-loyalist elements and other coup plotters within the military.